Dreadnought guitar top plate innovation - Jirásek, Ondřej (Studio D Akustika, 2024)
This paper describes the innovation of Dreadnought guitars, especially braces on top plate The goal was to increase the dynamic range of the instruments, not only in strength but also in spectral spread The prolongation of tones in the Sustain and Release phases was also important Mechanical and acoustic properties of instruments from Furch Guitars’ production were measured (Chladni figures, frequency response), numerical simulation of innovated top plate in program ANSYS was prepared (by the matrix) and the changes in organisation of ribs were proposed as following The new samples of innovated Dreadnought guitars were produced by the factory, again measured, analysed and evaluated.

This paper describes the innovation of Dreadnought guitars, especially braces on top plate The goal was to increase the dynamic range of the instruments, not only in strength but also in spectral spread The prolongation of tones in the Sustain and Release phases was also important Mechanical and acoustic properties of instruments from Furch Guitars’ production were measured (Chladni figures, frequency response), numerical simulation of innovated top plate in program ANSYS was prepared (by the matrix) and the changes in organisation of ribs were proposed as following The new samples of innovated Dreadnought guitars were produced by the factory, again measured, analysed and evaluated.
Dreadnought guitar top plate innovation
Keywords: acoustic; anechoic chambre; braces; compliance matrix; computer simulation; dreadnought guitar; frequency response; fast Fourier transform; Furch guitars; experiment; Chladni figures; nodal acceleration vector; nodal displacement vector; nodal velocity vector; measurement; Poisson’s number; relative strain; resonance modes; resulting strain vector; short time Fouri-er transform; soundboard; spectrograph; spectrogram; spectrum; stiffness matrix; structural damping matrix; structural mass matrix; structural stiffness matrix; SWEEP method; tensile stress; top plate; Young’s modulus of elasticity; vibration; acoustic; anechoic chambre; braces; compliance matrix; computer simulation; dreadnought guitar; frequency response; fast Fourier transform; Furch guitars; experiment; Chladni figures; nodal acceleration vector; nodal displacement vector; nodal velocity vector; measurement; Poisson’s number; relative strain; resonance modes; resulting strain vector; short time Fouri-er transform; soundboard; spectrograph; spectrogram; spectrum; stiffness matrix; structural damping matrix; structural mass matrix; structural stiffness matrix; SWEEP method; tensile stress; top plate; Young’s modulus of elasticity; vibration